198 Effectiveness of Surgical Revascularization for Stroke Prevention in Pediatric Patients With Sickle Cell Disease and Moyamoya Syndrome. (1st August 2016) - Yang, Wuyang; Porras, Jose Luis; Xu, Risheng; Garzon-Muvdi, Tomas; Caplan, Justin M.; Colby, Geoffrey P.; Coon, Alexander Lewis; Tamargo, Rafael J.; Huang, Judy; Ahn, Edward Sanghoon
Abstract: INTRODUCTION: Sickle cell disease (SCD) patients with moyamoya syndrome (MMS) represent a rare subset of patients with potentially devastating neurological outcomes. The effectiveness of surgical revascularization in this patient population is currently unclear. We aim to elucidate the effectiveness of surgical intervention in our series of SCD-MMS patients by comparing stroke recurrence in those undergoing revascularization vs conservative transfusion therapy. METHODS: We retrospectively reviewed our database of moyamoya patients at the Johns Hopkins Medical Institution from 1990 to 2013. Pediatric patients (age <18 years) with a confirmed diagnosis of SCD and MMS were included. Baseline and management information was described. Intracranial stroke occurrence during the follow-up period was compared between interventional and conservatively managed patients. RESULTS: A total of 15 pediatric SCD-MMS patients (28 affected hemispheres) were included in our study, and all were African American. Seven patients (14 hemispheres) were treated with indirect surgical revascularization. The average age at MMS diagnosis was 9.0 ± 4.0 years, with 9 (60.0%) being female. Fourteen (93.3%) patients had a stroke before diagnosis of MMS with average age at first stroke of 6.6 ± 3.9 years. During an average follow-up period of 11.6 years, 4 patients in the conservative treatment group experienced strokes in 5 hemispheres, whereas no patients undergoing the revascularization procedure had any strokes at follow-up ( P = .029). CONCLUSION: Our study suggests that indirect revascularization is a safe and effective alternative to best medical therapy in patients with SCD-MMS. Additional studies with larger sample sizes may further clarify optimal treatment regimens for this challenging group of patients.